Coronavirus Disease-2019 Conundrum: RAS Blockade and Geriatric-Associated Neuropsychiatric Disorders - de Miranda, Aline Silva; Teixeira, Antonio Lucio (Frontiers in Medicine, 2020)
Coronavirus Disease 2019 (COVID-19) is caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which primarily targets the human respiratory system and may lead to severe pneumonia and ultimately death. Mortality rate is particurlarly high among people beyond the sixth decade of life with cardiovascular and metabolic diseases. The discovery that the SARS-CoV-2 uses the renin-angiotensin system (RAS) component ACE2 as a receptor to invade host epithelial cells and cause organs damage resulted in a debate regarding the role of ACE inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) therapies during COVID-19 pandemic. Some authors proposed the discontinuation of ACEIs and ARBs for cardiovascular, kidney and metabolic diseases, while expert opinions have discouraged that due to limited empirical evidence of their negative effect on COVID-19 outcomes, and that withdrawing treatment may contribute to clinical decompensation in high-risk patients. Moreover, as cardiovascular and metabolic diseases are associated with neurodegenerative and psychiatric disorders, especially among older adults, a critical appraisal of the potential positive effects of ACEIs and ARBs is highly needed. Herein, we aim to discuss the conundrum of ACEIs and ARBs use in high-risk patients for COVID-19, and their potential protective role on the development and/or progression of geriatric neuropsychiatric disorders.